PENDUGAAN PARAMETER GENETIK TANAMAN CABAI KATOKKON (CAPSICUM CHINENSE JACQ) DENGAN IRADIASI SINAR GAMMA - Zulkifli Maulana (UPPM Politeknik Gorontalo, 2023)
Katokkon chili is local horticultural commodity originating from Toraja and is often called katokkon pepper. This chili has good adaptation with a fairly high yield. The people of Toraja and the surrounding area really like this type of chili because it has one of the advantages of a production period that is not too long, around 3-4 months after transplanting. The purpose of this study was to determine the effect of giving a dose of gamma ray irradiation on the genetic parameters of katokkon chili plants. The use of this research as a basis for developing and improving genetics in breeding katokkon chili plants eith a dose of gamma irradiation. The implementation of the research was carried out at BTP. Tamalanrea, Tamalanrea District, Makassar City, South Sulawesi and the Integrated Farming System Education Garden, on Jl. Raya Poros Sappaya, Bontoramba Village, Pallangga District, Gowa Regency, from March to July 2023. The plants came from the control treatment (D0) and 200 Gray (D1) consisted of 3 replicates for each treatment and each experiment consisted of 15 plants, so that the total number of plants in this study was 90 plants. The research was carried out in the form of a randomized block design (RBD) with a dose of gamma irradiation as the main factor. The results showed that gamma irradiation at doses of 200 Gray could have a genetic effect compared to D0 on flowering age, number of fruit planted, fruit diameter, fruit weight, fruit stalk diameter, fruit length and fruit flesh thickness.